(untitled) (Journal of Hama University, 2026)
The study aimed to identify the effectiveness of the learning strategy for mastery (Keller) in developing some creative thinking skills among fourth grade students in the subject of science. The research sample consisted of (60) male and female students for the experimental and control groups. The quasi-experimental approach was used and the test was used as a research tool. The results showed that there were statistically significant differences between the average scores of the experimental and control groups in the post-application in favor of the experimental group, and that there were statistically significant differences between the average scores of the experimental group in the pre- and post-applications in favor of the post-application .